Avaliação do processo de ensino: uma abordagem multivariada - Marchesan, Teresinha Maria (2006)
The practice of quality in university management is done with the engagement of all school community. Thus, through the evaluation of the teaching process, the present work aimed at identifying weak and strong points of teaching process based on student s opinion and using multivariate analysis. In this study questionnaires that included the following categories of variables were considered: 1) student s selfevaluation, 2) assessment of the content s importance to the course and the professor s pedagogical performance, 3) professor s assessment by students and 4) student s assessment by professor. The data obtained at the end of 2003 composed the first sample that represented a participation of 54% of students attending International Business Major. The data concerning the assessment processes carried out in the end of 2005 composed a participation of 87% of students enrolled in the undergraduate courses of the institution. The information was processed using the statistical technique of factorial analysis with normal varimax rotation. The factorial analysis resulted in factors with satisfactory internal consistency that define these dimensions: 1) situations of stimulus by the professor to student seeks knowledge with an explanation of 50%, 2) with 21% of explanation, students mentioned the relationship between content and course s objectives and their practical applications as satisfactory, 3) methodological situations appropriated to the learning and teaching processes with 11% of explanation and as a weak point in the teaching process, 4) interdisciplinarity was not perceived by students as really important and 5) attendance to library and reading habit must be more motivated as well as participation in congresses and research projects. Through the internal consistency of factors, the results showed the validity of the construct which supports the teaching processes of this institution. Thus, this way of analyzing data favors a better observation of managers about the student s perceptions of the teaching process in a specific situation, enabling to direct investments in search of quality.